Importance of Big Data in the Pharma Industry - Syed Shoeb Peer, K. Samunnisa, A. David Donald (Mathematical Statistician and Engineering Applications, 2023)
The term "big data" was first used to describe information sets that were too enormous to be captured, stored, managed, and analysed by conventional database systems. The concept of big data analytics is being implemented in many different industries today Analytics for large datasets are used to glean insights for businesses. Using big data analytics, one can gain insight into topics like market movements, consumer preferences, and other similar phenomena. Not only that, but this sort of analytics also makes important contributions to the decision-making procedure in business contexts. Step-by-step approaches exist for analysing huge data, and there are various approaches to choose from. The purpose of this essay is to introduce the concept of data analytics, explore its many manifestations, and investigate how it may be useful in the selection of generic medications.